A113 ANNUAL COLONOSCOPY VOLUME IS NOT PREDICTIVE OF COLONOSCOPY QUALITY - FINDINGS FROM THE SOUTHWEST ONTARIO COLONOSCOPY COHORT. (4th March 2021) - Sey, M; Siddiqi, O; McDonald, C; cocco, S; Hindi, Z; Rahman, H; Chakraborti, D; French, K; Alsager, M; Blier, M; makandey, b; Al-obaid, S; et al.
Abstract: Background: Performing a minimum number of colonoscopies annually has been proposed by some jurisdictions as a requirement for maintaining privileges. However, this practice is supported by limited evidence. Aims: The objective of this study was to determine if annual colonoscopy volume was associated with colonoscopy quality metrics. Methods: A population-based study was performed using the Southwest Ontario Colonoscopy cohort, which consists of all adult patients who underwent colonoscopy between April 2017 and Oct 2018 at 21 academic and community hospitals within the health region. Data were collected through a mandatory quality assurance form completed after each procedure and pathology reports were manually reviewed. Physician annualized colonoscopy volumes were compared by correlation analysis to each quality-related outcome, by means of the area under the receiver operating characteristics curve (AUROC), and logistic regression. The prognostic value of colonoscopy volume was also adjusted for case-mix and potential confounders in separate regression analyses for each outcome. The primary outcome was ADR. Secondary outcomes were polyp detection rate (PDR), sessile serrated polyp detection rate (SSPDR), and cecal intubation. Results: A total of 47, 195 colonoscopies were performed by 75 physicians (37.5% by gastroenterologists, 60% by general surgeons, 2.5% others). There were no clear relationships between annual colonoscopy volumes and study outcomes. Colonoscopy volume was not associated with ADR (OR 1.03, 95% CI 0.96–1.10, p=0.48) and corresponded to an AUROC not significantly different from the null (AUROC 0.52, 95% CI 0.43–0.61, p=0.65). Multi-variable regression adjusting for case-mix also demonstrated no predictive value of annual colonoscopy volume for the primary outcome (OR 1.03, 95% CI 0.94–1.12, p=0.55). Similarly, analyses of secondary outcomes failed to find an association between colonoscopy volume and PDR, SSPDR, or cecal intubation (Table 1). Conclusions: Annual colonoscopy volumes do not predict ADR, PDR, SSPDR, or cecal intubation rate. Results of unconditional and conditional approaches for examining the predictive value of annual colonoscopy volume for quality related outcomes. Funding Agencies: None